ANALYSIS OF MARKETING PERFORMANCE EFFECTIVENESS OF INSTAGRAM AND TIKTOK PLATFORMS (CASE STUDY OF ISDSHOP MAKASSAR) - Risnawati S; Muhammad Rakib; Muhammad Ashdaq (JURNAL KINDAI, 2026)
This study aims to assess the effectiveness of promotions using Instagram and TikTok in attracting audience attention. The formulation of the problem in this study are: 1) How to analyze the effectiveness of promotions using Instagram and TikTok on Isdshop Makassar, 2) What factors influence promotions using Instagram and TikTok on Isdshop Makassar. The objectives to be achieved are to find out: 1) Analysis of the effectiveness of promotions using Instagram and TikTok on Isdshop Makassar, 2) Factors that influence promotions using Instagram and TikTok on Isdshop Makassar. The approach used is a descriptive quantitative approach with data collection techniques used are documentation and observation techniques. The results of the study show that TikTok and Instagram are equally effective platforms and have advantages in improving digital marketing performance on ISDShop Makassar. The effectiveness of digital promotions is influenced by several factors including content creativity, upload frequency, interaction with the audience, selection of publication timing, and use of platform features.